Rapoport's Rule and the effect of the last glaciation upon elevational range size: An analysis using a dung beetle model (Coleoptera: Scarabaeidae: Onthophagus) in Mexican tropical mountains. (March 2022) - Kohlmann, Bert; Arriaga-Jiménez, Alfonsina; Portela Salomão, Renato
Several studies have tested the Elevational Rapoport Rule (ERR) in arthropods, especially in the Neotropical mountains. Nonetheless, different approaches should be used for a more nuanced comprehension of ERR patterns and assemblage altitudinal distribution patterns, such as the biogeographical, ecological, and evolutionary contexts. This study aims to test the ERR for elevational gradients in Mexican mountains. For this study, dung beetle assemblages of the genus Onthophagus were used as a model organism, and their distribution was studied in several different mountain ranges of the Mexican tropics. Altitudinal distribution of Onthophagus species was analyzed, including ecological traits and biogeographical/phylogenetical contexts as covariables. The increase of altitude was positively correlated to the assemblage altitudinal range. Furthermore, altitudinal range, relative abundance, body size, and mountain's topographic prominence were positively correlated to the mean altitudinal range of Onthophagus species. Nonetheless, different altitudinal relationships were observed, depending on the mountain. The results support the idea that species that inhabit higher altitudes appear to be more environmentally plastic and occur in wider altitudinal ranges than species from lower altitudes, thus supporting the ERR. The present findings stress that biogeographical, ecological, phylogenetical, and historical aspects, besides body size, are essential drivers of the altitudinal distribution of Onthophagus dung beetles.